EFEKTIVITAS METODE MNEMONIK TERHADAP DAYA INGAT SISWA PADA MATA PELAJARAN IPS KELAS V DI SDN KUTABUMI II KAB. TANGERANG - Rizki, Indah (JTIEE (Journal of Teaching in Elementary Education), 2020)
This study aims to determine whether there are differences in the memory of students who are given the mnemonic method with students who are given conventional methods in class V social studies subjects. The hypothesis proposed in this study is. "Is there a difference in memory between students who are given the mnemonic method and students who are given the conventional method". Methods of data collection are test and non-test (observation, interview and documentation). The statistical test used by using the t-test showed that the pretest of the experimental and control class was 1.1100 and the table was 2.01063. because tcount <t table or 1.1100 <2.01063 with a significance level of 0.05 then H0 is rejected. While the posttest of the experimental and control class was 16.8068 and the table was 2.01063. because tcount> ttable or 16.8068> 2.01063 with a significance level of 0.05 then H0 is accepted. Then the results of this study concluded that the mnemonic method was more effective on students’ memory on social studies subjects compared to conventional methods.